Consumer preference for bean attributes: a study in Kiambu county, Kenya - Gitonga, Hannah W. (Kenyatta University, 2013)
Common bean (Phaseolus Vulgaris L.) is an important legume that provides income and food in Kenya. The Kenyan bean market has a bean deficit of 10,800 metric tons. This is despite intensive breeding work that has resulted in bean varieties that are high yielders, superior in withstanding biotic and abiotic stresses. There should be a shift on how beans are produced if Kenya is expected to be self sufficient in bean production. Focus should shift from how much beans can be produced within a given area, as has been the case, to production of what is acceptable in the market by consumers. This study focused on consumer preference for common beans in two districts, Thika East and Thika West of Kiambu County. The two were chosen because of their high population, diverse socioeconomic characteristics of residents since the two districts had both rural and urban living setups. Questionnaires with structured and open ended questions were used to reach 212 consumers and 67 traders. A hedonic price model was used to analyse effect of preferred attributes on price. Results showed that beans were an important part of respondents diet with majority of respondents (86%) consuming beans more than once a week. Rural respondents consumed beans more frequently compared to urban respondents; difference in consumption was statistically significant (0.025). Beans were popular with women (83%) and were consumed by all age groups but there was more consumption in the 31-40 years age group (26.8%). GLP 585 was ranked 1st by 64.7% respondents, GLP 2 was ranked 2nd (43%) and KAT X56 was ranked 3rd (39.8%) respondents. GLP varieties were popular among urban respondents while rural respondents consumed both GLP and KAT varieties. Consumers had preference for Cooking quality, keeping quality, color, taste, low flatulence and grainsize attributes associated with GLP 585, KAT X56 and GLP 2 varieties. Cooking quality and keeping quality were important attributes consumers considered when making purchase decisions. They were willing to pay a premium for color and discount for flatulence of KAT X56. They were willing to pay a premium for taste and discount for grainsize of GLP 585. These results suggest efforts should be focused on improvement of these attributes. Exploration of other factors that effect price consumers would be willing to pay for a variety should be undertaken. Promotion campaigns should be undertaken to create awareness of nutritional value of beans. Value chain analysis of beans to come up with ready to use products with high nutritional value is recommended.